EFFECT ON SURGICAL MARGINS FOLLOWING FORMALIN FIXATION - Dr Parnika Garg; Dr Neeraj Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The surgical margin is an important prognostic factor in predicting the local recurrence of colorectal cancer. The current guidelines recommend a 5cm margin both proximally and distally for colon cancers and a distal resection margin of 1-2cm for mid and low rectal cancers. Although surgical margins are an important predictor for local recurrence, it is not routinely recorded in a fresh specimen prior to formalin fixation.Methods: Retrospective analysis of prospectively collected data of patients undergoing colorectal surgery January 2012 to December 2021. Specimens were measured fresh by one surgeon immediately following extraction. This measurement was compared with measurement performed by the pathologist after formalin fixation. The remaining data were collected retrospectively.Results: A total of 177 patients with a median age of 64 years old (range 27–87) underwent colorectal surgery . Following formalin fixation, the median total specimen length (TSL) shrinkage was 34.98% and distal resection margin (DRM) shrinkage was 40%. Following formalin fixation, 69.6% of colon cancer specimens met the recommended resection margin of 5 cm. On the other hand, 95.6% of rectal cancer specimens met the DRM recommendation of 1 cm. There were no local recurrences during the median follow up period of 202 weeks (range 33-523 weeks).Conclusions: Marked shrinkage of colorectal cancer specimens can occur following formalin fixation.Documentation of surgical margins immediately following extraction is important to ensure adherence to current guidelines. Local recurrences are rare with current margin recommendations.